Hemispheric Brain Activation in Young Adults While Performing OrthographicTasks Using fMRI - Acosta-Franco, J. A.; Flores Saiffe-Farías, A.; Gómez-Velázquez, F. R.; González-Garrido, A. A.; Romo-Vázquez, R. C. (Revista Mexicana de Ingenieria Biomedica, 2019)
The written language domain is based on the consolidation of complex neural representations of words' ortho-graphic patterns. Here, we studied the characteristics and differences of the neural activation levels that occur in the neural processes related to orthographic specialization, with functional magnetic resonance imaging, in each hemisphere, of 27 young adults with low and high orthographic abilities when they performed orthographic tasks. The results suggest that in high-orthographic-performance participants’ left hemispheric neural activation does not vary between words and pseudohomophones; otherwise, their neural activation variates in incorrect vs. correct responses. There were not found interhemispheric differences in low-orthographic-performance participants whe-re they performed any type of task. There were some tendency in the low-orthographic-performance participants to have greater neural activation dispersion, regarding the high-orthographic-performance participants, in both hemispheres, also, there were found tendency in low-orthographic-performance participants to have greater neu-ral activation variation in explicit tasks; nevertheless, there is not enough conclusive statistic evidence. This study increases the evidence of lateralized neural specialization of orthographic abilities.